Analysis of Job Design and Work Environment on Human Resource Development at PT Berkat Samudra Gemilang Lines - Agunawan; Rahayu, Sri; Anwar, Yohny (International Conference Epicentrum of Economic Global Framework, 2026)
This study aims to analyze the influence of job design and work environment on human resource development at PT Berkat Samudra Gemilang Lines. A quantitative research approach was employed using a survey method involving company employees as respondents. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that job design and work environment have a positive and significant effect on human resource development. Effective job design, supported by a conducive work environment, enhances employees' competencies, productivity, and overall performance. The study concludes that improving job structures and workplace conditions is essential for strengthening sustainable human resource development and organizational competitiveness.